2017
DOI: 10.1134/s0012496617030048
|View full text |Cite
|
Sign up to set email alerts
|

Peptides semax and selank affect the behavior of rats with 6-OHDA induced PD-like parkinsonism

Abstract: Parkinson's disease (PD) is the second most common severe neurodegenerative disorder that is characterized by progressive degeneration of dopaminergic neurons (DA neurons) in the substantia nigra pars compacta (SNpc) region of the brain. In the present study, we investigated the effects of the synthetic regulatory peptides Semax (analog of an ACTH 4-10 fragment (ACTH4-10)) and Selank (analog of immunomodulatory taftsin) on behavior of rats with 6-hydroxidopamine (6-OHDA) induced PD-like parkinsonism. It was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Semax activity in above models is possibly defined by its influence on cognitive processes and is not connected (on receptor level) with anxiety and depression components. In the induced PD‐like Parkinsonism model, Semax (in contrast to anxiolytic peptide Selank) was also inactive . For now, we found the only stress model, which fits the pointed before (anti‐anxiety) requirements—a model of chronic unpredictable stress in rats (based on two modified well‐known stress models).…”
Section: Discussionsupporting
confidence: 54%
“…Semax activity in above models is possibly defined by its influence on cognitive processes and is not connected (on receptor level) with anxiety and depression components. In the induced PD‐like Parkinsonism model, Semax (in contrast to anxiolytic peptide Selank) was also inactive . For now, we found the only stress model, which fits the pointed before (anti‐anxiety) requirements—a model of chronic unpredictable stress in rats (based on two modified well‐known stress models).…”
Section: Discussionsupporting
confidence: 54%
“…6‐OHDA is a common neurotoxin, with important applications in the establishment of PD models, which can damage dopaminergic neurons and cause PD‐like behavioral changes (Slominsky et al., 2017). In this study, we found that the mechanism of 6‐OHDA‐induced neuronal injury is associated with ROS‐NLRP3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that Selank did not cause adverse reactions and tolerance and did not have a withdrawal effect [3,10]. Clinical trials of Selank confirmed its neuroprotective and anxiolytic effects, as well as its nonspecific activating effect, mainly on the frontal lobes of the cerebral cortex [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, brain tissues are characterized by high metabolic rate and low rate of cell regeneration. The brain requires about 30% of the oxygen consumed by the body, and its tissues are highly sensitive to hypoxia and ischemic disorders [12]. Accordingly, an increased production of reactive oxygen species, along with a disorder of the antioxidant defense system, are among the leading mechanisms of cell damage in TBI [20].…”
Section: Discussionmentioning
confidence: 99%